Au@Ag core/shell cuboids and dumbbells: Optical properties and SERS response. (December 2015) - Khlebtsov, Boris N.; Liu, Zhonghui; Ye, Jian; Khlebtsov, Nikolai G.
Abstract: Recent studies have conclusively shown that the plasmonic properties of Au nanorods can be finely controlled by Ag coating. Here, we investigate the effect of asymmetric silver overgrowth of Au nanorods on their extinction and surface-enhanced Raman scattering (SERS) properties for colloids and self-assembled monolayers. Au@Ag core/shell cuboids and dumbbells were fabricated through a seed-mediated anisotropic growth process, in which AgCl was reduced by use of Au nanorods with narrow size and shape distribution as seeds. Upon tailoring the reaction rate, monodisperse cuboids and dumbbells were synthesized and further transformed into water-soluble powders of PEGylated nanoparticles. The extinction spectra of AuNRs were in excellent agreement with T-matrix simulations based on size and shape distributions of randomly oriented particles. The multimodal plasmonic properties of the Au@Ag cuboids and dumbbells were investigated by comparing the experimental extinction spectra with finite-difference time-domain (FDTD) simulations. The SERS efficiencies of the Au@Ag cuboids and dumbbells were compared in two options: (1) individual SERS enhancers in colloids and (2) self-assembled monolayers formed on a silicon wafer by drop casting of nanopowder solutions mixed with a drop of Raman reporters. By using 1, 4-aminothiophenol Raman reporter molecules, the analytical SERS enhancement factor (AEF) of the colloidal dumbbells was determined to be 5.1×10 6, which is an order of magnitude higher than the AEF=4.0×10 5 for the cuboids. This difference can be explained by better fitting of the dumbbell plasmon resonance to the excitation laser wavelength. In contrast to the colloidal measurements, the AEF=5×10 7 of self-assembled cuboid monolayers was almost twofold higher than that for dumbbell monolayers, as determined with rhodamine 6G Raman reporters. According to TEM data and electromagnetic simulations, the better SERS response of the self-assembled cuboids is due to uniform packing and more efficient generation of electromagnetic hot spots, as compared to the dumbbell monolayers. Highlights: Au@Ag core/shell cuboids and dumbbells are fabricated in colloid and powder form. T-matrix and FDTD simulations are used to describe multimodal extinction spectra. SERS enhancement of colloidal dumbbells is an order higher than that for cuboids. SERS enhancement of self-assembled cuboids is twofold higher than that for dumbbells. FDTD simulations elucidate the physical origins of the different SERS efficiencies.